2012
DOI: 10.4269/ajtmh.2012.12-0136
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Melioidosis Treated with Cotrimoxazole Alone for Eradication Therapy

Abstract: Abstract. We retrospectively reviewed a 10-year experience of administration of cotrimoxazole alone in 31 patients compared with 109 patients who received conventional eradication therapy (cotrimoxazole plus doxycycline). The baseline characteristics, the clinical manifestations, the initial intravenous antibiotic treatments, and the mean duration of eradication therapy between the two groups were similar. The culture-confirmed recurrences among the patients who received cotrimoxazole alone and those who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Co-trimoxazole alone has been used for several years for the eradication phase of treatment in northern Australia with apparently excellent results [45] . In 2013, a group from southern Thailand published their experience of using co-trimoxazole alone, with similarly good results [46] . In a retrospective review over a 10-year period, only 1 (3.2%) of 31 patients who received co-trimoxazole alone relapsed compared with 5 (4.6%) of 109 treated with co-trimoxazole plus doxycycline.…”
Section: Treatmentmentioning
confidence: 99%
“…Co-trimoxazole alone has been used for several years for the eradication phase of treatment in northern Australia with apparently excellent results [45] . In 2013, a group from southern Thailand published their experience of using co-trimoxazole alone, with similarly good results [46] . In a retrospective review over a 10-year period, only 1 (3.2%) of 31 patients who received co-trimoxazole alone relapsed compared with 5 (4.6%) of 109 treated with co-trimoxazole plus doxycycline.…”
Section: Treatmentmentioning
confidence: 99%
“…This recommendation has not been tested in a clinical trial evaluating patient outcome. Alternatively, using the dosage of 160/800 mg twice daily for three months has been shown to be effective in eradication of the infection [ 70 ].…”
Section: Reviewmentioning
confidence: 99%
“…Such adverse reactions often results in a switch to second-line treatment (usually amoxicillin-clavulanic acid), which is strongly associated with an increased risk of relapse 6 . Findings from a descriptive 10 year cohort study done in Australia reported recurrent infection in less than 2% of patients (one of 60 patients) who had oral treatment with TMP-SMX alone; 8 TMP-SMX has since become the standard regimen in Australia 3 and is occasionally used in Thailand 9 . We proposed that TMP-SMX alone was an adequate treatment for melioidosis, and did a clinical trial to compare the efficacy and safety of TMP-SMX versus TMP-SMX plus doxycycline for the oral treatment phase of melioidosis.…”
Section: Introductionmentioning
confidence: 99%